2012
DOI: 10.4236/jbbs.2012.24058
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Upregulates Hippocampal GAP-43 Level of Aged Rats with Enhanced Spatial Memory and Behavior Response

Abstract: Rehmannia glutinosa is a traditional Chinese medical herb and has a long history in cognitive deficits therapy. Its therapeutic efficacy has been confirmed by clinical studies. In this study, we attempted to investigate the effects of catalpol, an iridoid from Rehmannia glutinosa, on cognitive and behavioral function of aged rats with memory loss. 22 -24 month Sprague-Dawley spontaneous rats of memory loss with aging were selected by step-down type passive avoidance test and randomly allocated to two groups: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Although catalpol and puerarin are of promoting angiogenesis and neural plasticity after brain stroke, the mechanisms are different. Bodies of reports confirmed that catalpol-induced this neural generation is relative to VEGF 52 and GAP-43 54 which haven't been proved to be involved in puerarin-induced angiogenesis; while in aspect of anti-inflammation, more articles are focused on puerarin which inhibits inflammation through lowering IL-6 and IL-1β 55 . Hence, it seems that there is synergistic effect between catalpol and puerarin in neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Although catalpol and puerarin are of promoting angiogenesis and neural plasticity after brain stroke, the mechanisms are different. Bodies of reports confirmed that catalpol-induced this neural generation is relative to VEGF 52 and GAP-43 54 which haven't been proved to be involved in puerarin-induced angiogenesis; while in aspect of anti-inflammation, more articles are focused on puerarin which inhibits inflammation through lowering IL-6 and IL-1β 55 . Hence, it seems that there is synergistic effect between catalpol and puerarin in neuroprotection.…”
Section: Discussionmentioning
confidence: 99%